Report on participation in Kenya agriculture sector Pre-SB58 country strategy meeting - Sarku, Rebecca; Whitfield, Stephen (2023)
Kenya therefore is of the view that the implementation of agriculture and food security issues in the Sharm -El Sheikh Joint Work on Implementation of climate action on agriculture and food security requires: enhance support of the means of implementation through coordinated actions, and partnerships that will support context-specific policies and measures, driven by science, and local and Indigenous knowledge.